2022
DOI: 10.1111/jcal.12728
|View full text |Cite
|
Sign up to set email alerts
|

Does the emotional design of scaffolds enhance learning and motivational outcomes in game‐based learning?

Abstract: Background: In recent years, the importance of emotions in learning has been increasingly recognized. Applying emotional design to induce positive emotions has been considered a means to enhance the instructional effectiveness of digital learning environments. However, only a few studies have examined the specific effects of emotional design in game-based learning.Objectives: This quasi-experimental study utilized a value-added research approach to investigate whether emotional design applied to scaffolding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…For instance, higher task difficulty is related to higher state anxiety or worry. This aligns with research in another motivational framework, situational interest, in which multiple factors affect situational interest towards mathematical tasks including, individual interest, task difficulty, and competence beliefs (Høgheim & Reber, 2019;Koskinen et al, 2023). Yet, more research is needed examining which task characteristics could affect the relation between state anxiety and mathematical performance.…”
Section: Introductionsupporting
confidence: 81%
“…For instance, higher task difficulty is related to higher state anxiety or worry. This aligns with research in another motivational framework, situational interest, in which multiple factors affect situational interest towards mathematical tasks including, individual interest, task difficulty, and competence beliefs (Høgheim & Reber, 2019;Koskinen et al, 2023). Yet, more research is needed examining which task characteristics could affect the relation between state anxiety and mathematical performance.…”
Section: Introductionsupporting
confidence: 81%
“…The game-based task version used in this study was based on the Number Trace game [ 10 ], which uses (fraction) number line estimation tasks as its core learning (game) mechanic. The current version of the game was specifically created for fMRI and NIRS research.…”
Section: Methodsmentioning
confidence: 99%
“…A game-based implementation of the number line estimation task typically includes game elements such as a narrative and virtual incentives, while a non-game-based task version does not include such game elements. Studies employing game-based number line estimation tasks for fraction learning reported significant increases in performance reflecting improvements in participants’ fraction understanding [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of multimedia learning, emotional design has been found to increase learners' positive affect, enjoyment, mental effort, intrinsic motivation, and learning gains (Wong & Adesope, 2021). A recent game-based learning study showed that the emotional design of scaffolding increased players' situational interest and self-efficacy (Koskinen et al, 2022).…”
Section: Game-based Learningmentioning
confidence: 99%